Keeping toxigenic Aspergillus section Flavi and aflatoxin contamination at bay by deploying atoxigenic-based biocontrol products during production of groundnut and maize in Mozambique - Augusto, J.; Atehnkeng, J.; Ortega-Beltran, A.; Cotty, P.J.; Bandyopadhyay, R. (Frontiers Media, 2024)
Aflatoxins, produced by aflatoxigenic Aspergillus section Flavi fungi, commonly occur in groundnut and maize grown in Mozambique and have long been associated with high prevalence of liver cancer, stunting, and restricted access to lucrative international markets. Effective aflatoxin control options in the country are limited and not adequately explored. Biocontrol products based on atoxigenic strains of A. flavus provide viable aflatoxin mitigation measures but require development for Mozambique. Four hundred and sixty-eight (468) and 558 groundnut and maize farmers, respectively, voluntarily evaluated the effectiveness of two biocontrol products (Aflasafe MWMZ01 and Aflasafe MZ02), each containing as active ingredients four distinct atoxigenic isolates of A. flavus belonging to native vegetative compatibility groups (VCGs), at preventing aflatoxin contamination and displacement of aflatoxigenic fungi for 2 years in various agro-ecologies. Most groundnut and maize treated with the biocontrol products were below maximum levels for food in the European Union (EU; 85%; p < 0.01) and the United States (US; 99%; p < 0.01). In contrast, most non-treated maize and groundnut (ranging from 38 to 70%; p = 0.05) were above the EU and US maximum allowable levels for food. Aflatoxin reductions ranged from 78 to 98% (p < 0.01) in treated groundnut, and from 61 to 93% (p < 0.01) in treated maize. Toxigenic fungi were almost completely displaced from soils and crops by the applied atoxigenic active ingredients. This study revealed that the atoxigenic based biocontrol technology is effective in Mozambique at displacing aflatoxigenic fungi and reducing aflatoxin accumulation in both groundnut and maize but a combination with other management tools is encouraged for better retention of crop quality along the value chain.